Records Committee review for rare bird sighting of Lesser Black-backed Gull near the Ben Butterworth Parkway, 1987 - Fuller, Charleset al (1987)
Records Committee review for a Lesser Black-backed Gull near the Ben Butterworth Parkway in Rock Island County, IL on February 4, 1987. Includes a record review document with votes and two documentation forms submitted to the committee. Epson - sheet feed